Spermatozoa Develop Molecular Machinery to Recover From Acute Stress - Starovlah, Isidora M.; Radovic Pletikosic, Sava M.; Tomanic, Tamara M.; Medar, Marija LJ.; Kostic, Tatjana S.; Andric, Silvana A. (Frontiers in Endocrinology, 2022)
This study was designed to search for the possible mechanism(s) of male (in/sub)fertility by following the molecular response of spermatozoa on acute psychological stress (the most common stress in human society) and on 20-hours-time-dependent-recovery-period. To mimic in vivo acute stress, the rats were exposed to immobilization once-for-3-hours. The recovery periods were: 0 (immediately after the stress and 3 hours after the light is on - ZT3), 8 (ZT11), 14 (ZT17), 20 (ZT23) hours after the stress. Results showed that the acute stress provoked effects evident 20 hours after the end of stress period. Numbers of spermatozoa declined at ZT17 and ZT23, while functionality decreased at ZT3 and ZT11, but recovered at ZT17 and ZT23. Transcriptional profiles of 91% (20/22) of tracked mitochondrial dynamics and functionality markers and 91% (20/22) signaling molecules regulating both mitochondrial dynamics and spermatozoa number/ functionality, were disturbed after the acute stress and during the recovery period. Most of the changes represented as increased transcription or protein expression at ZT23. The results of PCA analysis showed clear separation of acute-stress-recovery effects during active/dark and inactive/light phases. The physiological relevance of these results is the recovered functionality, suggesting that molecular events are an adaptive mechanism, regulated by acute-stress-response signaling. Results of PCA confirmed the separation of the effects of the acute-stress-recovery on gene expression related to mitochondrial dynamics, cAMP and MAPK signaling. The transcriptional patterns were different during the active and inactive phases. Most of the transcripts were highly expressed during the active phase, which is expected given that stress occurred at the beginning of the inactive phase. According to the best of our knowledge, our results provide a completely new view and the first presentation of the markers of mitochondrial dynamics network in spermatozoa and their correlation with signaling molecules regulating both, mitochondrial dynamics and spermatozoa number and functionality during recovery from the acute stress. Besides, the interactions between the proteins important for spermatozoa homeostasis and functionality (MFN2 and PRKA catalytic subunit, MFN2 and p38MAPK) are shown for the first time. Accordingly, the mitochondrial dynamics markers or their transcriptional profiles could be a possible predictors of (in/sub)fertility.